(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The mass media have a significant influence on the formation and adoption of gender stereotypes in the mass consciousness, because today they are not only an important public institution, but also a channel for the transmission and reception of information. That is why now they are considered as one of the levers of influence on mass public consciousness. Consequently, gender images and stereotypes, which are found in advertising texts and plots, take root in the minds of ordinary citizens. The article describes the main trends in the development of gender stereotypes in modern advertising; the problem of stereotypical thinking in society, are common social stereotypes and fixed in the public consciousness the images of men and women in the former-Soviet Union on a material of Kazakhstan, Russia and Ukraine. In order to study the construction of gender images and stereotypes in modern advertising practice, we implemented sampling analysis examples print (magazine) advertising in magazines, various country affiliations, published in Russian language. Key words: advertising, advertising space, gender stereotypes, gender images, gender roles, gender marking.